Civil gang abatement: the effectiveness and implications of policing by injunction - Allan, Edward L. (Criminal justice, 2004)
Introduction -- Theoretical perspectives -- Legal perspectives -- The gang injunction -- The dimension of flexiblity -- The dimension of community involvement -- Policy implications.